Analisis tingkat kepuasan pasien penyakit ginjal kronis terhadap pelayanan hemodialisis di RSUD Raa Soewondo Pati - Natalie, Michelle Ruth; Saryatmo, Mohammad Agung (Universitas Tarumanagara, 2024)
This study aims to analyze the level of satisfaction of chronic kidney disease (CKD) patients with hemodialysis services at RSUD RAA Soewondo Pati as well as the quality of hemodialysis services themselves, and determine the relation between the level of satisfaction of CKD patients and the quality of hemodialysis services provided. The form of research used was quantitative descriptive with a cross-sectional study design, with a total research sample of 90 CKD patients undergoing hemodialysis at RAA Soewondo Pati Regional Hospital. Data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The data in this research was analyzed in three stages, namely: outer model analysis, inner model analysis, and hypothesis testing. The results obtained from data analysis found that there was a positive influence from the indicators of physical evidence, reliability, responsiveness, assurance, and empathy on the satisfaction of CKD patients undergoing hemodialysis at RAA Soewondo Pati Regional Hospital with the hope of improving service performance in the future, as an effort and contribution to improving the quality of life of CKD patients. Penelitian ini bertujuan untuk menganalisis tingkat kepuasan pasien penyakit ginjal kronis (PGK) terhadap pelayanan hemodialisis di RSUD RAA Soewondo Pati serta kualitas pelayanan hemodialisis itu sendiri, dan mengetahui hubungan antara tingkat kepuasan pasien PGK dengan kualitas pelayanan hemodialisis yang disediakan. Bentuk penelitian yang digunakan, yaitu deskriptif kuantitatif dengan desain studi cross-sectional, dengan jumlah sampel penelitian sebanyak 90 pasien PGK yang menjalani hemodialisis di RSUD RAA Soewondo Pati. Analisis data dilakukan dengan metode Partial Least Square-Structural Equation Modelling (PLS-SEM). Data dalam penelitian ini dianalisis dalam tiga tahapan, yaitu: analisis outer model, analisis inner model, serta pengujian hipotesis. Hasil yang didapatkan dari analisis data, yaitu ditemukan bahwa terdapat pengaruh positif dari indikator tangibles, reliability, responsiveness, assurance, dan empathy terhadap kepuasan pasien PGK yang menjalani hemodialisis di RSUD RAA Soewondo Pati dengan harapan agar dapat meningkatkan kinerja pelayanan di masa yang akan datang, sebagai salah satu upaya dan kontribusi dalam memperbaiki kualitas hidup para pasien PGK tersebut.